Pengaruh Makro Ekonomi, PBV, Struktur Kepemilikan, dan Kinerja Keuangan Terhadap Nilai Perusahaan: Studi pada Perusahaan Tekstil yang Terdaftar di BEI Pada Tahun 2021-2022 - Krisogonus Avio Seleman; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to determine the effect of macroeconomics on financial performance, ownership structure, and firm value as well as the effect of financial performance, PBV, and ownership structure on firm value. The population in this study is textile companies listed on the Indonesia Stock Exchange. Samples were collected from 10 textile companies listed on the Indonesia Stock Exchange during the 2021-2022 period. The data analysis technique uses descriptive statistics using the SmartPLS4 application. The results of this study indicate an insignificant effect of macroeconomics on financial performance, ownership structure and firm value. A significant effect of financial performance is also obtained, while macroeconomics, PBV, and ownership structure have no significant effect on firm value.